A theoretical reference frame for "school development" - Reinbacher, Paul (Swiss Journal of Educational Research, 2018)
The field of «school development» is an area hard to overlook at best, mined at worst – widely dominated by normative recommendations for practitioners on the one hand and by inductive experiences derived from this practice on the other hand. Apart from either empirical generalisations or rather eclectic «bricolage» with theoretical approaches drawing from different disciplinary backgrounds, one enters a zone still lacking a larger integrative theoretical framework. Such a scheme is to be developed here in the tradition of T. Parsons and H. Fend, striving for a consideration of the different elements of educational action systems in their individual and collective dimension, an integration of the different levels of educational systems, and finally an embedment of school development processes in the context of comprehensive societal structures.